2002
DOI: 10.1002/jrs.926
|View full text |Cite
|
Sign up to set email alerts
|

The role of specific normal modes during non‐Born–Oppenheimer dynamics: the S1–S0 internal conversion of β‐carotene interrogated on a femtosecond time‐scale with coherent anti‐Stokes Raman scattering

Abstract: The population flow from the first excited singlet state (S 1 ) to the electronic ground state (S 0 ), facilitated through the S 1 -S 0 internal conversion, and the subsequent internal vibrational energy redistribution and vibrational cooling processes are monitored selectively with respect to the different forms of nuclear motion in all-trans-b-carotene. This is realized by exciting the molecule into the second excited singlet state (S 2 ) with an auxiliary pump laser pulse and interrogating the population re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 50 publications
3
51
1
Order By: Relevance
“…The maximum enhancement of |ρ 12 | results in 1.6, and for ρ 33 + ρ 44 is 2.1. Of relevance, however, is the maximum enhancement factor in |ρ 34 |, which becomes in this case 38.5. This large value is observed close to the resonance of the first vibrational upper state level, with ν 19,365 cm −1 and for two almost symmetric chirp values, namely φ −210 fs 2 and φ 220 fs 2 (see Figure 6).…”
Section: Influence Of the Laser Peak Intensitymentioning
confidence: 92%
See 3 more Smart Citations
“…The maximum enhancement of |ρ 12 | results in 1.6, and for ρ 33 + ρ 44 is 2.1. Of relevance, however, is the maximum enhancement factor in |ρ 34 |, which becomes in this case 38.5. This large value is observed close to the resonance of the first vibrational upper state level, with ν 19,365 cm −1 and for two almost symmetric chirp values, namely φ −210 fs 2 and φ 220 fs 2 (see Figure 6).…”
Section: Influence Of the Laser Peak Intensitymentioning
confidence: 92%
“…This result is partially in accordance with the studies made in [60], where it is shown that excited state vibrational coherences are enhanced predominantly by positively chirped pulses. Figure 4b shows the evolution in time of the coherence |ρ 34 | at the relevant parameter values. It is clear that the two chirped pulses after the interaction of the first half of the pulse are able to retain the |ρ 34 | coherence as compared to the TL pulse.…”
Section: Appl Sci 2016 6 351mentioning
confidence: 99%
See 2 more Smart Citations
“…Within the overall pump-probe scheme a wide variety of different techniques has been developed including, e.g. time-resolved resonance Raman [6], pump-CARS (coherent anti-Stokes Raman scattering) [35][36][37], fluorescence upconversion (see, for example, [38]), macrocrystalline time-resolved X-ray scattering [39], photoelectron spectroscopy [40] and -perhaps most commonly applied -time-resolved transient absorption [41].…”
Section: Transient Absorptionmentioning
confidence: 99%